Density-functional study of pressure-induced phase transitions and electronic properties of Zn2V2O7. Issue 18 (10th March 2021) - Díaz-Anichtchenko, Daniel; Gracia, Lourdes; Errandonea, Daniel
Abstract : Phase transitions induced by pressure in zinc pyrovanadate have been understood using density-functional theory calculations. Consequences of structural changes on electronic properties are discussed. Abstract : We report a study of the high-pressure behavior of the structural and electronic properties of Zn2 V2 O7 by means of first-principle calculations using the CRYSTAL code. Three different approaches have been used, finding that the Becke–Lee–Yang–Parr functional is the one that best describes Zn2 V2 O7 . The reported calculations contribute to the understanding of previous published experiments. They support the existence of three phase transitions for pressures smaller than 6 GPa. The crystal structure of the different high-pressure phases is reported. We have also made a systematic study of the electronic band-structure, determining the band-gap and its pressure dependence for the different polymorphs. The reported results are compared to previous experimental studies. All the polymorphs of Zn2 V2 O7 have been found to have a wide band gap, with band-gap energies in the near-ultraviolet region of the electromagnetic spectrum.